Přínosy letecké dopravy na udržitelný rozvoj v Pardubickém regionu - Jindrová, Pavla; Dušková, Anna (Univerzita Pardubice, 2010)
The problems of air traffic together with environmental and economic aspects are discussed in this article, particularly in case of a specific situation of Pardubice airport. The importance of air traffic for Pardubice region is analyzed as well as the estimation of effectiveness of new airport terminal, using the enumeration of possible benefits and costs. The possible negative effects of air transportation on human health in the consequence of a new airport terminal construction in Pardubice are also being analyzed.
Keywords: air traffic; airport terminal; environmental aspects; economic aspects; SWOT; cost benefit analysis